2015
DOI: 10.3201/eid2102.141449
|View full text |Cite
|
Sign up to set email alerts
|

Influenza D Virus in Cattle, France, 2011–2014

Abstract: A new influenza virus, genus D, isolated in US pigs and cattle, has also been circulating in cattle in France. It was first identified there in 2011, and an increase was detected in 2014. The virus genome in France is 94%–99% identical to its US counterpart, which suggests intercontinental spillover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
4
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(181 citation statements)
references
References 9 publications
5
166
4
6
Order By: Relevance
“…This result conflicts somewhat with our surveillance findings and those of others (3,4,6,7) showing that IDV associates with disease in the field. We hypothesize that the minimal amounts of damage seen in experimentally infected calves might induce inflammation (IDV infection induced neutrophil extravasation and migration into tracheal epithelium in our infected animals) that could facilitate coinfections with other bovine pathogens.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This result conflicts somewhat with our surveillance findings and those of others (3,4,6,7) showing that IDV associates with disease in the field. We hypothesize that the minimal amounts of damage seen in experimentally infected calves might induce inflammation (IDV infection induced neutrophil extravasation and migration into tracheal epithelium in our infected animals) that could facilitate coinfections with other bovine pathogens.…”
Section: Discussioncontrasting
confidence: 57%
“…Our virologic surveillance found that IDV was present in 23.6% of 55 calves affected with BRD but in only 2.4% of 82 healthy calves upon arrival at the same facility (4). Other studies have shown that the IDV positivity rates in cattle with BRD in the United States and France were 4.5% and 4.8%, respectively (3,6). The prevalence of IDV in China among healthy adult cattle populations was reported to be 0.7% (7).…”
mentioning
confidence: 84%
“…The detection of high antibody titers and the relative ease of virus isolation from cattle have led to the thesis that cattle may be the natural IDV reservoir (2)(3)(4)(5)(6)(7). Based on those assertions, serology studies have focused on cattle (2)(3)(4)(5)(6). A serology study of animals in calving operations in Mississippi found 94% seroprevalence among neonatal beef calves (10).…”
Section: Resultsmentioning
confidence: 97%
“…The estimated seroprevalence of IDV among US cattle herds is 88% (5,9), and 2% in farmed American swine (2). The detection of high antibody titers and the relative ease of virus isolation from cattle have led to the thesis that cattle may be the natural IDV reservoir (2)(3)(4)(5)(6)(7). Based on those assertions, serology studies have focused on cattle (2)(3)(4)(5)(6).…”
Section: Resultsmentioning
confidence: 97%
“…Wirus ten posiada szeroki zakres geograficzny występowania. Izolowano go w USA, Kanadzie, Chinach, a w Europie -we Francji oraz we Włoszech, co wskazuje, że doszło do jego transmisji międzykontynentalnej (1,4,(6)(7)(8)20).…”
Section: Zakażenia Bydła Idvunclassified